Pengembangan Aplikasi Badstics untuk Menentukan Karakteristik Pemain Bulu Tangkis Menggunakan Metode Naive Bayes (Studi Kasus : PBSI Jawa Timur) - Robihamanto Robihamanto; Adam Hendra Brata; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In a game of badminton, the coach plays an important role to give the athlete advises, and supervision during the game of badminton. A coach needs to know exactly the characters of their rival. To have a character means to have sense of adamancy, goodness, praiseworthiness, and dependability, and also have moral principles. Characteristics of players is important to know, because when in the current game the player already knows what to give to the athlete so that the athlete can win the game, in the implementation of the player feature can be seen from the action done in the field that has been done with the manual that is with the recording game , then a video recording and then write it a document that takes up to 3 hours 4 hours for one game. So it takes an application to fulfill the needs of the coaches and provide information and characteristics of the players on the field when the game is in progress. This application is made with the expectation that the coach can know the characteristics of the opponent and can provide referrals based on the statistics of the players when in field. This application was built using the iOS. In the calculations process, the characteristic classification using naive bayes which is a classification method that used the concept of opportunity, where it is assumed that each attribute example (data sample) are off to each other based on the class attributes. This method is chosen because it requires only a small amount of training data to estimate the parameters (average and variance of variables) required for classification. In this study, the results of the test using post-test study with the method of System Usability Scale is 86.5 which means entering into the category of certified-density on demand.